Perspectives of Children From Refugee Backgrounds on Their Family Storytelling as a Culturally Sustaining Practice. Issue 1 (2nd January 2019) - Strekalova-Hughes, Ekaterina; Wang, X. Christine
ABSTRACT: Foregrounding the lived experiences and voices of children from refugee backgrounds, the authors adapted culturally sustaining pedagogy and refugee critical race theory frameworks to investigate how Nepali, Somali, and South Sudanese children from refugee backgrounds whose families resettled in western New York perceive family storytelling. The authors analyzed their perspectives based on interviews of siblings following family storytelling at their houses. The authors found that the children in this study intuitively identified unique ways of family telling stories (e.g., remembering and repeated storytelling, narrative structure, and performative nuances) and internalized family storytelling as an important culturally and linguistically sustaining practice. In addition, the children made powerful connections between family and school storytelling practices (e.g., suggesting cross-cultural literacy strategies, identifying common genres, and noticing similar values taught at both settings). However, they also identified challenges to incorporating family storytelling at school, including the loss of native languages and the need for more knowledge of the stories' cultural context among peers. The authors draw implications for culturally sustaining pedagogy and research.